Geosynthetics: Leading the Way to a Resilient Planet PROCEEDINGS OF THE 12TH INTERNATIONAL CONFERENCE ON GEOSYNTHETICS (12ICG), SEPTEMBER 17-21, 2023, ROMA, ITALY. - Biondi, Giovanni; Cazzuffi, Daniele; Moraci, Nicola; Soccodato, Claudio (Taylor & Francis, 2023)
This volume contains the proceedings of the 12th International Conference on Geosynthetics (12 ICG), held in Roma, Italy, 17-21 September 2023. About 750 Authors - Academics, Researchers, Students, Practitioners, Contractors and Manufacturers - contributed to the peer-reviewed papers of this volume, which includes the Giroud lecture, the Bathurst lecture, the Rowe lecture, four keynote lectures and 296 technical papers. The content of these proceedings illustrates the sustainable use of geosynthetics in a variety of innovative as well as consolidated applications. After the sustainability implications in the correct use of geosynthetics, the ability to overcome the natural events effects, often related to the climate change, and to adequately afford the human activities (as the increase of pollution) forced to refer to a new keyword: Resiliency. The 12 ICG intends to become the base for the next step, hence the conference theme is 'Geosynthetics, Leading the Way to a Resilient Planet'. The conference topics, through general and parallel sessions, invited presentations and keynote lectures, address the most recent developments in geosynthetic engineering, and stimulate fruitful technical and scientific interaction among academicians, professionals, manufacturers, students. The 12 ICG proceedings contain a wealth of information that could be useful for researchers, practitioners and all those working in the broad, innovative and dynamic field of geosynthetics.